May Measurement Month 2017: an analysis of blood pressure screening results worldwide. Issue 7 (July 2018) - Beaney, Thomas; Schutte, Aletta E; Tomaszewski, Maciej; Ariti, Cono; Burrell, Louise M; Castillo, Rafael R; Charchar, Fadi J; Damasceno, Albertino; Kruger, Ruan; Lackland, Daniel T; Nilsson, Peter M; Prabhakaran, Dorairaj; et al.
Summary: Background: Increased blood pressure is the biggest contributor to the global burden of disease and mortality. Data suggest that less than half of the population with hypertension is aware of it. May Measurement Month was initiated to raise awareness of the importance of blood pressure and as a pragmatic interim solution to the shortfall in screening programmes. Methods: This cross-sectional survey included volunteer adults (≥18 years) who ideally had not had their blood pressures measured in the past year. Each participant had their blood pressure measured three times and received a a questionnaire about demographic, lifestyle, and environmental factors. The primary objective was to raise awareness of blood pressure, measured by number of countries involved, number of people screened, and number of people who have untreated or inadequately treated hypertension (defined as systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg, or both, or on the basis of receiving antihypertensive medication). Multiple imputation was used to estimate the mean of the second and third blood pressure readings if these were not recorded. Measures of association were analysed using linear mixed models. Findings: Data were collected from 1 201 570 individuals in 80 countries. After imputation, of the 1 128 635 individuals for whom a mean of the second and third readings was available, 393 924 (34·9%) individuals had hypertension. 153 905 (17·3%) of 888 616 individuals who were not receiving antihypertensive treatment were hypertensive, and 105 456 (46·3%) of the 227 721 individuals receiving treatment did not have controlled blood pressure. Significant differences in adjusted blood pressures and hypertension prevalence were apparent between regions. Adjusted blood pressure was higher in association with antihypertensive medication, diabetes, cerebrovascular disease, smoking, and alcohol consumption. Blood pressure was higher when measured on the right arm than on the left arm, and blood pressure was highest on Saturdays. Interpretation: Inexpensive global screening of blood pressure is achievable using volunteers and convenience sampling. Pending the set-up of systematic surveillance systems worldwide, MMM will be repeated annually to raise awareness of blood pressure. Funding: International Society of Hypertension, Centers for Disease Control and Prevention, Servier Pharmaceutical Co.